The effectiveness of alternative listening devices to conventional hearing aids for adults with hearing loss: a systematic review protocol - Maidment, David W.; Barker, Alex; Xia, Jun; Ferguson, Melanie A. (BMJ Publishing Group, 2016)
Introduction Hearing loss is a major public health concern, affecting over 11 million people in the UK. While hearing aids are the most common clinical intervention for hearing loss, the majority of people that would benefit from using hearing aids do not take them up. Recent technological advances have led to a rapid increase of alternative listening devices to conventional hearing aids. These include hearing aids that can be customised using a smartphone, smartphone-based ‘hearing aid’ apps, personal sound amplification products and wireless hearing products. However, no systematic review has been published evaluating whether alternative listening devices are an effective management strategy for people with hearing loss.